X-Ray Technology to Evaluate Mortality of Covid-19 Patients in Comorbid Diabetes Mellitus and Stroke - Asmiati Amir; Muhammad Yunus; Muh Fachrul Latief; A Indra Wulan Sari Ramadani (Akademi Teknologi Industri Dewantara Palopo, 2021)
Mortality evaluation of Covid-19 patients in comorbid diabetes mellitus and stroke using x-ray technology. Examining patients using an x-ray was carried out in the radiology room at one of the Covid-19 referral hospitals in Makassar. The patient data used is Covid-19 mortality data, namely January-June 2021. Diabetes mellitus and stroke comorbidities significantly affect the mortality of Covid-19 patients. Comorbid diabetes mellitus has a significant effect on the mortality of Covid-19 patients. The age group ≥ 61 years old is exposed to Covid-19 and has a high mortality rate.